2020
DOI: 10.1186/s13014-020-01602-7
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison between RapidArc and HyperArc techniques in salvage stereotactic body radiation therapy for recurrent nasopharyngeal carcinoma

Abstract: Background: To evaluate dosimetric differences of salvage irradiations using two commercially available volumetric modulated arc therapy (VMAT) stereotactic body radiation therapy (SBRT) techniques: RapidArc (RA) and HyperArc (HA), for recurrent nasopharyngeal carcinoma (NPC) after initial radiation therapy. Methods: Ten patients with recurrent NPC status previously treated with radiation therapy were considered suitable candidates for salvage SBRT using VMAT approach. Two separate treatment plans were created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Another distinguishing advantage of HA-S is consistently reducing the radiation dose to multiple OARs, including dose to the brainstem, brain V24, V12, V5, eyes, and lens, comparing to coplanar RA. Similar findings have been demonstrated that HA has some advantage over RA for intracranial brain metastasis treatment 17 , 19 , 22 , 23 and extracranial 41 treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Another distinguishing advantage of HA-S is consistently reducing the radiation dose to multiple OARs, including dose to the brainstem, brain V24, V12, V5, eyes, and lens, comparing to coplanar RA. Similar findings have been demonstrated that HA has some advantage over RA for intracranial brain metastasis treatment 17 , 19 , 22 , 23 and extracranial 41 treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Despite encouraging dosimetric quality of DTRT plans and the promise of deliverability on standard C-arm linacs [6,12], it remains a research topic for HN radiotherapy and is not yet clinically available. Nasopharyngeal and cranial tumours have often been investigated owing to the large collision-free space [7,11,12] with statictable non-coplanar solutions already commercially available on C-arm linacs [13,14]. Large HN target volumes are often associated with high rates of toxicity and could benefit from DTRT but these have a more caudal isocenter.…”
Section: Open Accessmentioning
confidence: 99%
“…According to statistics, on average, one out of 17 women worldwide develops BC in their whole life, and the majority of the patients with breast malignant tumor are the ones with hormone receptor-positive breast cancer, which account for about 65% [ 6 ]. Ho et al [ 7 ] have stated that BC is the most prevalent malignant tumor among women, and its incidence, which has been increasing in recent years, accounts for 14% of all malignant tumors in the female body. According to pertinent literature, the BC incidence among Asian women increased by approximately 1.7% per year from 2006 and 2015, so it is urgent to provide effective treatment for BC patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%